Surface modification of ZnO by plasma and laser treatment. (17th February 2017) - Afanasjev, V. P.; Mukhin, N. V.; Redka, D. N.; Rudenko, M. V.; Terukov, E. I.; Oseev, A.; Hirsch, S.
ABSTRACT: Structural and optical properties of zinc oxide thin films deposited on glass substrates were studied before and after plasma and laser treatment. It was shown that the polycrystalline ZnO structure was destroyed by modifying laser radiation, while in the center of the spot amorphous zinc oxide was formed. Plasma treatment performed a transformation of the surface morphology of ZnO layers without deterioration of their optical and electrical properties. Longer treatment times result in over flattening of the surface followed by observable reduction of light scattering along with degradation of electronic properties.